Watching lymphocytes work: Advances in imaging meet immunological challenges - Burack, W; Dustin, M (2000)
Synapses are basic units of cell-cell communication in the nervous and immune systems. The internal workings of these molecular machines have been glimpsed through advances in imaging and biochemical technologies. Here, the promise of emerging fluorescence microscopy approaches to further clarify the molecular organization of immunological synapses is discussed.